PENGARUH PENGALAMAN AUDIT DAN KEAHLIAN AUDIT TERHADAP KUALITAS HASIL PEMERIKSAAN - Aang Syahdina (Jurnal Akuntansi Bisnis, 2017)
This study aims to test the influence of empirical experience and expertise to the Quality Auditor examination results in the Inspectorate General of Ministry of Health of the Republic of Indonesia. Population study of 200 respondents based on employment data Inspectorate General of Ministry of Health of the Republic of Indonesia in 2009. By using the technique non-probability sampling the number of questionnaires that Return of 135 questionnaires, but only 122 questionnaires were deemed eligible for further analyzed. Result of this research findings, that: (1) auditor experience variables explain variations in the quality of the best audit results of more than 29 percent with the alpha level of less than 0.01. Variable coefficients auditor marked positive experience with the results of the t test showed that alpha level of less than 0.01. This means that the quality of audit results will be increased with the number of auditor experience, both related to the number of the assignment, the task force is audited, the audit task complexity and that experienced by auditors, (2) that expertise auditors also have a positive and significant effect on the quality of results audit. Regression analysis related hypothetical second test of this research result in adjusted R2 of 0.314, which means about 31 percent of audit quality variation explained by factors expertise auditors. Variable coefficients are positive auditor expertise and significant at the alpha level of less than 0.01. In general, two conclusions of this research is consistent with the results of previous research. Results of this research is also in line with the standards and normative provisions that apply this regard technical expertise and non-technical and experience requirements as for someone to say professionals in the field of auditing. (3) This study also found that together the expertise and experience of auditors and the significant positive effect on the quality of examination results. Multiple Regression is used to test the hypothetical third of this research indicates that the variable experience of auditors and auditor expertise together explain variations in the quality of audit results of more than 41 percent of the F test showed that alpha levels below 0.01. All coefficients are independent variables with a positive test result indicates a level of alpha is less than 0.01. The findings confirm that this expertise includes technical skills and non-technical as well as the same importance in improving the quality of audit results.  Keywords: non-probability sampling, auditor experience, auditor experience, the quality of audit results